Simulation training enables emergency medicine providers to rapidly and safely initiate extracorporeal cardiopulmonary resuscitation (ECPR) in a simulated cardiac arrest scenario. (May 2019) - Whitmore, Sage P.; Gunnerson, Kyle J.; Haft, Jonathan W.; Lynch, William R; VanDyck, Tyler; Hebert, Christopher; Waldvogel, John; Havey, Renee; Weinberg, Allison; Cranford, James A.; Rooney, Deborah M.; Neumar, Robert W.
Abstract: Background: Extracorporeal cardiopulmonaryresuscitation (ECPR) is emerging as a viable rescue strategy for refractory out-of-hospital cardiac arrest. In the U.S., limited training of emergency medicine providers is a barrier to widespread implementation. Aims: Test the hypothesis that emergency medicine physicians and nurses can acquire and retain the skills to rapidly and safely initiate ECPR using high-fidelity simulation. Study design: Prospective interventional study. Setting: U.S. tertiary academic medical center. Subjects: Emergency medicine physicians and nurses with no prior ECPR/ECMO experience. Methods: Teams of three physicians and three nurses underwent a two-day ECPR training course including didactics, hands-on training, and simulation. Teams were videotaped initiating ECPR in a high-fidelity simulation scenario before and after simulation training. The primary outcome was the proportion of simulations in which full ECPR support was achieved within 30 min of patient arrival. Results: Five teams completed the entire study. Full ECPR support was achieved within 30 min of patient arrival in 11/15, 15/15, and 15/15 attempts at baseline (B), post-testing (PT) and 3-month post-testing (3-PT), respectively ( p = 0.06). Intervals (mean ± sd) required to achieve full ECPR support at B, PT, and 3-PT were 25.8±5.3, 17.2±4.6, and 19.2±1.9 min respectively ( p < 0.05 for B vs. PT and 3-PT). Conclusion: High fidelity simulation training is effective in preparing emergency medicine physicians and nurses to rapidly and safely initiate ECPR in a simulated cardiac arrest scenario, and should be considered when implementing an ED-based ECPR program.